An Advanced Multifunctional Hydrogel‐Based Dressing for Wound Monitoring and Drug Delivery. Issue 19 (25th September 2017) - Mirani, Bahram; Pagan, Erik; Currie, Barbara; Siddiqui, Mohammad Ali; Hosseinzadeh, Reihaneh; Mostafalu, Pooria; Zhang, Yu Shrike; Ghahary, Aziz; Akbari, Mohsen
Abstract: Wound management is a major global challenge and poses a significant financial burden to the healthcare system due to the rapid growth of chronic diseases such as diabetes, obesity, and aging population. The ability to detect pathogenic infections and release drug at the wound site is of the utmost importance to expedient patient care. Herein, this study presents an advanced multifunctional dressing (GelDerm) capable of colorimetric measurement of pH, an indicator of bacterial infection, and release of antibiotic agents at the wound site. This study demonstrates the ability of GelDerm to detect bacterial infections using in vitro and ex vivo tests with accuracies comparable to the commercially available systems. Wireless interfaces to digital image capture hardware such as smartphones serve as a means for quantitation and enable the patient to record the wound condition at home and relay the information to the healthcare personnel for following treatment strategies. Additionally, the dressing is integrated within commercially available patches and can be placed on the wound without chemical or physical irritation. This study demonstrates the ability of GelDerm to eradicate bacteria by the sustained release of antibiotics. The proposed technology holds great promise in managing chronic and acute injuries caused by trauma, surgery, or diabetes. Abstract : The ability to detect pathogenic infections and release drug at the wound site is of the utmost importance to expedient wound management. Herein, this study presents an advanced multifunctional dressing (GelDerm) capable of colorimetric measurement of pH, an indicator of bacterial infection, and release of antibiotic agents at the wound site.